Customer Satisfaction on Services offered by Pos Laju Sungai Merah, Sibu, Sarawak / Aja Langgit - Langgit, Aja (Universiti Teknologi MARA Sarawak,Kampus Samarahan, 2015)
This research was to determine and analyse the service quality and customer satisfaction toward the Pos Laju. This research was to identify and assess the customer perception and overall satisfaction level of customer toward the service offered by Pos Laju, Sibu. The study was used a questionnaire to gain the result related to customer satisfaction. 400 of questionnaires were estimated but only 350 of questionnaires have been collected to analyze which to determine the result. SPSS programme (Statistical Software Package) was used to identify and test the research objective in the research. The findings indicate the Reliability dimension is the most important dimension followed by tangible, empathy and responsiveness, while assurance is found out least significant to the customer in Pos Laju, Sibu, Sarawak. In addition, customer satisfaction was found that low relationship between theory of SERVQUAL model toward customer satisfaction. Generally the study implies the Pos Laju should take workable measures to improve upon their services quality in specific areas. It is recommended that further research should assess and analyse customer satisfaction with specific services across Pos Laju in Sibu, Sarawak.